Elastic and plastic deformation behavior of helium nano-bubbled single crystal copper: An atomistic simulation study - Neogi, Anupam; Askari, Hesam; Abdolrahim, Niaz (Journal of nuclear materials, 2021)
The mechanical properties, particularly, yield strength and ductility of metals, exposed under irradiation usually degrade due to generation of primary and secondary defects such as dislocations, vacancies, gas-bubbles, etc. Using atomistic simulations, we have shown that irradiation-induced Helium gas-bubbles are not always detrimental and can contribute to the plastic deformation that leads to improved strength and ductility of the host metal. However, the inter-bubble distance plays a strong role on controlling the mechanisms that operate during elastic and plastic deformation. When the inter-bubble distance is comparatively low (order of 3–4 nm), the copper nanopillar hosting He gas-bubbles exhibits lower yield strength but improved strain hardening rate, and ductility, via coalescence of bubbles that leads to a homogeneous plastic flow. In contrast, higher inter-bubble distance, order of 10 nm, shows a higher yield stress, large stress drop after yielding, and shear localization via shear band formation and bubble fragmentation. Similar inter-bubble distance dependent plasticity mechanisms in He nano-bubbled copper have also been observed in recent in-situ transmission electron microscopy experiments.